The impact of musical expertise and directional isotropy on the proportions and magnitudes of pitch-shift responses in glissandos - Li-Hsin Ning (Frontiers in Psychology)
BackgroundPrevious studies have established that when vocal pitch in auditory feedback is perturbed unexpectedly, speakers typically produce opposing responses to correct the perceived error. Investigations comparing steady-pitch vocalizations and non-steady-pitch vocalizations have revealed that the extent of compensation is task-dependent. Nevertheless, the influence of musical expertise and the preference for adopting opposing or following responses during glissando vocalizations remain unexplored.MethodsIn this study, thirty-six native Mandarin speakers, comprising equal numbers of musicians and non-musicians, were asked to perform three vocal tasks. During the sustained vowel task, participants maintained a steady and comfortable pitch while vocalizing /a/ for 3 s. In the upward glissando and downward glissando tasks, participants imitated the gliding pattern of the model note introduced at the beginning of each trial. The onset of pitch-shifted feedback (±100 cents) occurred randomly between 500 and 700 ms after vocal onset, lasting for 200 ms. Response proportions for opposing and following responses were estimated through Bayesian Poisson regression modeling, whereas response magnitudes were scrutinized using generalized additive mixed effects modeling.ResultsOur results revealed that opposing and following responses were less pronounced among musicians compared to non-musicians. Furthermore, following responses were not a minority in response to auditory perturbations; rather, they constituted 42% of the responses on average. Additionally, response magnitudes were found to be contextually sensitive and were influenced by the direction of the shift and the intended pitch direction.ConclusionOur results indicate that our ability to control vocal responses is influenced by context and that musicial training plays a role in affecting how participants react to auditory perturbations.